CANCER NOMENKLATURE AND SUSTAINED PROLIFERATIVE SIGNALING - Raxmonov Shoxzodbek Oybek o’g’li (Web of Journals Publishing, 2025)
Cancer is a leading cause of suffering and death in the developed world. It is now understood that cancer is a collection of more than 100 different diseases, each caused by a specific and often unique age-related accumulation of genetic and epigenetic alterations. Environment, heredity, and behavior interact to modify the risk of developing cancer and the response to treatment. Improvements in treatment strategies and supportive care, coupled with new, often individualized therapies based on advances of the basic pathophysiology of malignancy, have contributed to an increasing number of effective options for these diverse, often lethal disorders collectively called cancer.
Keywords: Cancer, rhabdomyosarcoma, guanine diphosphate (GDP), epidermal growth factor (EGF), guanine triphosphate (GTP).